Constructionist assessment with mobile software-based paper prototyping - Mohamedally, Dean; Zaphiris, Panayiotis (My University, 2008)
Low-fidelity prototyping is a Knowledge Elicitation technique in HumanComputer Interaction (HCI). However, empirical methods for low-fidelity prototyping have remained relatively static in development. We describe artefact-driven dynamic constructionism, allowing us to view the temporal evolution of design artefacts as measurable constructs within low-fidelity prototypes. Two mobile software tools are described, PROTEUS and PROTEUS EVALUATOR, using Social Constructionism. HCI class prototyping exercises with the tools are reported with 40 HCI Postgraduate students. Artefact-driven constructionist metrics are thus applied to low-fidelity prototyping pedagogy. Advantages and disadvantages of using such methods are demonstrated and explained.
Keywords: Paper prototyping; Mobile knowledge elicitation; Mobile learning; M-learning; HCI; Human-computer interaction; Low-fidelity prototyping; Design artefacts; Mobile software; Social constructionism; Higher education